Metagenome-assembled genomes reveal novel diversity and atypical sources of a superbug - Rafael López-Sánchez; Alejandro Aguilar-Vera; Santiago Castillo-Ramírez (Microbiology Spectrum)
ABSTRACT The genomic epidemiology of Acinetobacter baumannii has been based on culture-dependent whole-genome sequencing. However, this approach neglects sources that are not amenable to microbial culture. Here, we show that metagenome-assembled genomes (MAGs) are useful in appraising the neglected diversity of A. baumannii from unconventional sources. We analyzed 22 MAGs in the context of genomes from the main human international clones and some animal and plant isolates. Given the known ecology of the species, some of these MAGs came from unexpected sources, such as the New York City subway or a kitchen counter. Our global phylogeny, with 240 genomes, demonstrated that although some MAGs were associated with some human international clones, most of them were not and were distantly related to the human clones. Furthermore, we found that these MAGs have antibiotic-resistance genes. Our results show that many MAGs represent novel lineages with some important resistance genes coming from unexpected sources. Our work illustrates a powerful approach to studying the neglected diversity of this superbug from uncommon sources. We anticipate that in the coming years, MAGs will be employed to analyze unconventional sources for other important superbugs.IMPORTANCEThe genomic epidemiology of Acinetobacter baumannii has been based on cultivated bacterial isolates. This disregards A. baumannii diversity from sources not amenable to microbial culture. In this study, we demonstrate that metagenome-assembled genomes (MAGs) are very helpful in assessing the understudied diversity of A. baumannii from atypical sources. Our results show that many MAGs represent novel lineages with important resistance genes coming from unexpected sources. We anticipate that in the coming years, approaches similar to ours will be employed to delve into different sources for other important superbugs.